Analysis of Property Marketing Strategy by Utilizing Digital Marketing (Case Study of PT Rizki Mandiri) - Cici Winda Atila; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
Digital marketing has now penetrated several fields, including property. Therefore, it is important for companies to implement digital marketing strategies for broader marketing. The company optimizes online marketing or digital marketing as a way of communicating with target consumers. This is definitely a very effective option. The purpose of this research is to find out how PT Rizki Mandiri Barokah can use digital marketing to increase sales. This study uses a qualitative method with a descriptive approach which was developed to provide information. Data collection techniques used in documentation and interviews. The results of this study are PT Rizki Mandiri Barokah implementing the right marketing strategy through digital real estate marketing to increase real estate sales and make a significant contribution to sales and reach many customers.